2017
DOI: 10.1002/chem.201703704
|View full text |Cite
|
Sign up to set email alerts
|

Atomic/Molecular Layer Deposition of s‐Block Metal Carboxylate Coordination Network Thin Films

Abstract: We present novel atomic/molecular layer deposition (ALD/MLD) processes for the fabrication of crystalline inorganic-organic coordination network thin films with different s-block elements. Terephthalic acid is employed as the organic precursor. Such thin films could enable for example, next-generation battery, sensor and gas-storage technologies. The deposition processes fulfill the basic principles of ALD/MLD-type growth including the sequential self-saturated gas-surface reactions and atomic/molecular-level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
88
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 39 publications
(93 citation statements)
references
References 37 publications
5
88
0
Order By: Relevance
“… Summary of the s‐block metal 3,5‐PDC films realized in this study, and the corresponding TPA thin films reported earlier: crystalline films are indicated in green and amorphous films in striped gray. We also give the density values (in g cm −3 ) determined for each thin‐film sample from the critical angle value in the XRR pattern.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“… Summary of the s‐block metal 3,5‐PDC films realized in this study, and the corresponding TPA thin films reported earlier: crystalline films are indicated in green and amorphous films in striped gray. We also give the density values (in g cm −3 ) determined for each thin‐film sample from the critical angle value in the XRR pattern.…”
Section: Resultsmentioning
confidence: 89%
“…The GPC values were calculated from the X‐ray reflectivity (XRR)‐determined film thickness values; an example of a typical XRR curve is shown in the inset of Figure c. From Figure b it can be seen that the GPC value is well saturated when the Mg(thd) 2 pulse length is 5 s (subsequent N 2 purge length 5 s) and the 3,5‐PDC precursor pulse length is 15 s (subsequent N 2 purge length 30 s). It should be mentioned that very similar pulse length values are typically used for many other organic precursors in ALD/MLD processes . We then fixed these pulse/purge lengths for the rest of the experiments.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[25] In ALD/MLD the metal-organic material is grown from two mutually reactive gaseous precursors sequentially pulsed into the reactor chamber with an intermediate inert-gas purging step.L ike in the case of the parent ALD (atomic layer deposition) technology for simple inorganic materials,t his results in self-limited gas-surface reactions and consequently in the atomic/molecular level control of the growing thin-film material on the chosen substrate surface. [28][29][30][31] Herein we report the ALD/MLD growth of crystalline iron-azobenzene thin films in which the azobenzene moieties are an integral part of the crystal framework. [28][29][30][31] Herein we report the ALD/MLD growth of crystalline iron-azobenzene thin films in which the azobenzene moieties are an integral part of the crystal framework.…”
mentioning
confidence: 99%